Assessing Cilacap State Polytechnic Students' Ability to Conduct English Proficiency Test: Challenges and Strategies - Widianingsih, Betti; Vikasari, Cahya; Hazrina, Fadhillah; Prabowo, Annas Setiawan (JADEs Journal of Academia in English Education, 2025)
The purpose of this study was to evaluate Cilacap State Polytechnic students' readiness for the EPT-P and determine the obstacles they encounter as well as the strategies they employ to pass the test. This research used a mixed-methods case study design. To collect data, it used test and questionnaires which refer to the theory of Self-Regulated Learning, Test Taking Strategy, TAM and study of interlanguage. Analysis was based on Likert scale responses. It involved 60 final-year students of Cilacap State Polytechnic in the academic year of 2021/2022 from different study programmes. The study found that students at the State Polytechnic of Cilacap had a general lack of English competence, with just 25 out of 60 (41%) scoring over the 400 EPT-P pass score. Key issues were linguistic difficulties 37 students (62%) struggled with long reading texts, 41 (68%) struggled with essay writing, and 40 (67%) had difficulty listening, with 17 (28%) strongly agreeing. Psychological challenges were particularly significant: 28 students (47%) reported anxiety, while 44 (73%) reported losing focus. Technological and resource challenges were prominent, with 40 students (67%) lacking preparation materials and 55 (92%) never having had official instruction. Furthermore, 33 students (55%) considered the listening equipment unclear, and 54 (90%) thought the test was overpriced. Only 16 students (27%) prepared mentally and physically, while only 9 (15%) took classes. These findings, which were backed by many language learning and educational theories, emphasise the importance of economical training, easily accessible materials, and personalised coaching in improving student performance.